Análisis de riesgo de plagas para la actualización de requisitos fitosanitarios de frutos frescos de Naranja (citrus sinensis) y Limon (citrus limon) provenientes de Colombia. - Iturralde Ayala, María José (2010)
Ecuador several years ago faced increasingly difficult problems to control the entry of quarantine pests, because there was no adequate intervention in border areas, today the situation is different since the Ecuadorian Agency for Quality Assurance del Agro (AGROCALIDAD) is the National Organization for Phytosanitary Protection ONPF as an official entity that regulates phytosanitary aspects in the country and must respond to various commitments established in the International Convention on Plant Protection (CIPF), the Agreement for the Application of Sanitary and Phytosanitary Measures (SPS) in the context of the World Trade Organization (WTO), which establishes the Basic Rights and Obligations, by which members have the right to adopt the sanitary and phytosanitary measures necessary to protect the health and life of people and of animals, or to preserve vegetables. The basic objective is to maintain the sovereign right of each country to provide itself an “adequate level of protection” (or “acceptable level of risk”), ensuring at the same time that this right is not being misused for protectionist purposes and will not create unnecessary barriers. to trade, if they have no scientific justification That is why the study carried out is based on identifying quarantine pests that affect citrus fruits grown in our country, since the Ecuadorian Coast has enormous potential to produce citrus both for domestic supply and for export, thanks to favorable climate and soil conditions. This is why the main activity is to protect the sovereignty of the country, since with the entry of new pests, it could affect small producers, with the decrease in production hectares and in the future there would be the risk of depending on the importation of These two fruits, this shows the need to increase and improve citrus production and quality, based on better management in orchards.